ANALITICAL HIERARCHY PROCESS PENENTUAN KELAYAKAN PEMBERIAN PINJAMAN KREDIT USAHA RAKYAT BANK BRI MALAKA: ANALYTICAL HIERARCHY PROCESS DETERMINING THE FEASIBILITY OF PROVIDING PEOPLE'S BUSINESS CREDIT LOANS BANK BRI MALAKA - Luruk, Densi; Blegur, Fried Markus Allung; Dethan, Nugraha Kristiano Floresda; Fitriani (Journal of Mathematics Theory and Applications, 2025)
Kredit usaha rakyat (KUR) is a program launched by the government but the source of funds comes entirely from banks. Bank BRI Malaka is one of the banks trusted by the government to provide KUR facilities to the public.the increasing public interest in getting KUR, makes it difficult for banks to determine who is eligible to receive KUR or not. To overcome these problems, it is necessary to have a method that can provide recommendations for making the right decisions for prospective customers. This study aims to apply the Analytic Hierarchy Process (AHP) method in determining the priority order of selecting prospective customers by comparing one customer with another. The criteria to be considered are credit status, business conditions, income, guarantees and the number of customers involved in this study as many as 15 prospective customers. Data collection in this study was carried out by distributing questionnaires to 5 Mantri Bank BRI Malaka who were tasked with surveying the 15 prospective customers. Data is processed using the AHP method. AHP is used to produce a more consistent order of priority of each alternative. From the results of the analysis with AHP, 10 prospective customers were obtained in the highest order of priority who deserved to be given a KUR loan.